Pengaruh ROA, CAR, BOPO, FDR, Dan Inflasi Terhadap Pembiayaan Bermasalah (NPF) Di Bank Umum Syariah - Laili Isnaini; Slamet Haryono; Ibnu Muhdir (Universitas Hamzanwadi, 2021)
This study aims to examine the effect of ROA, CAR, BOPO, FDR, and inflation on problem financing. The data used are monthly data from 2015 to 2020 in August and Islamic Commercial Bank data obtained from the OJK. Data analysis was performed using the eviews 10 program. The results showed that ROA, CAR, FDR, BOPO, and inflation together had an influence on NPF and were able to explain the dependent variable by 87.68% and the remaining 12.32% was explained by other variables that influence NPF. ROA and FDR have no effect on NPF with a probability value higher than 0.05, while the independent variable that has a positive effect on NPF is BOPO, while the CAR and inflation variables have a negative effect on NPF with a probability value below 0.05